Analisis Usability Aplikasi Mobile Pemesanan Layanan Taksi Perdana Menggunakan Metode Webuse dan Heuristic Evaluation - Iunike Kartika Dewi; Yusi Tyroni Mursityo; Rekyan Regasari Mardi Putri (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Perdana Group is a taxi service provider that have launched a mobile application for online taxi booking in an attempt to compete with its competitor. The Perdana Taxi application was created with interface for taxi users dan drivers to ease the process of ordering taxi service. However the usability of both application interfaces itself have not been measured, therefore an usability evaluation was needed in order to measure the usefulness of the applications. The evaluation was also aimed to search for any usability problem in the applications. WEBUSE method was used to measure the usability level of both applications from their users, and search for any existing difficulties faced by their users by using the task scenario and a questionnaire which summarized from four usability variables. In order to explore the usability problems experienced by the users, an analysis was conducted based on questionnaire, testing, and evaluation results. Heuristic evaluation was also conducted to support the WEBUSE result and further dig through usability problems in the applications by using Nielsen heuristic by appointed evaluators. Result shows that overall, both application interfacess have â€œGOODâ€ usability level even though there are some problem related to content, button and in application navigation. Some heuristic principal was also violated on both applications that most related to error prevention. Usability problems found on both evaluation then was given improvement recomendations to increase the usability level.